Distorted Korean Idol’s Scandal, Deceitful Media, and The Role of Forensic Linguistics - Vivian Zulfie; Asrumi Asrumi; Agus Sariono (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
A celebrity’s scandal can be an enthralling theme for the media to produce news, either factual or fabricated. This research primarily focuses on distorted content or media manipulation to report it. It explores the correlation between misleading news and the motives behind twisted reality. The method used in this research is a descriptive qualitative method through the lens of the forensic linguistics approach, supported by Villa’s interpretative pragmatics (2010). The collected data were from selected sources of distorted media reporting, especially about a highly considered Korean singer’s crime, known Seungri of Bigbang. His charge was not direct link with sexual abuse and systematic drugs, which is in fact unrevealed wealthy people committing them. Even nonconsensual disclosure of sexually-explicit videos was committed by other celebrities. Yet, the media fraudulently blended and misrepresented Seungri as the key figure of the scandal in a club named ‘Burning Sun’. Society was misled to hate and blame him. This research shows that passive constructions, lexical references, and subject matters of the texts become linguistic evidence of fact distortion. Manipulating celebrity’s scandal is driven by political goals, such as creating mistrust and bewildering larger audiences, especially in South Korea about proving the justice system as the actual culprits are withdrawn. This research is noteworthy since there are interwoven claims of the power of media to wriggle out of legal punishments after spreading distorted facts. Hence, it implies that pragmatics is applicable and efficacious to prove the case. It leads to defamation by media, correlated with forensic linguistics. To reveal the distorted facts by deceitful media, this study expectantly contributes in enhancing social awareness of the truth behind blatant public outrage and its social consequences.